Hemagglutination, serum resistance, cell surface hydrophobicity and ESBL production among uropathogenic Escherichia coli - Javed, Saima; Iftikhar, Sidra; Anwer, Yusra; Pirzada, Zaid Ahmed (International Journal of Pathology, 2024)
Background: Bacteria have adapted with increased pathogenesis and drug resistance mechanisms to overcome host defense systems. Uropathogenic E. coli (UPEC) responsible for symptomatic Urinary tract infections (UTIs) carry diverse virulence factors and extended-spectrum beta-lactamase (ESBL) production which play a pivotal role in pathogenesis and antibiotic resistance. This study aimed to determine the phenotypic expression of virulence factors; i.e., Hemagglutination, serum resistance, cell surface hydrophobicity, and resistance factor ESBL production among UPEC isolates.Methods: In this prospective study 50 drug-resistant UPEC strains were evaluated for hemagglutination by slide method, cell surface hydrophobicity by salt aggregation test, serum resistance by serum bactericidal assay, and ESBL detection by double disc synergy test. Results: Among 50 UPEC strains 46 (92%) showed mannose-resistant hemagglutination, 48 (96%) were found to be serum resistant, 40 (80%) isolates were positive for cell surface hydrophobicity, while 43 (86%) were ESBL producers. Most of the UPEC that expressed virulence factors were ESBL producers as well.Conclusion: Overall, this study indicated that drug resistant UPEC isolates have expressed several virulence factors with ESBL production. This explains how pathogens have increased their virulence and resistance repertoire resulting in treatment failures.